The effects of different types of Tai Chi exercise on anxiety and depression in older adults: a systematic review and network meta-analysis - Kuang, Xiaoqin; Dong, Yangjian; Song, Long; Dong, Lili; Chao, Guodong; Zhang, Xinxin; Yang, Jiefu (Frontiers in Public Health, 2024)
i. Background: The body of evidence supporting the beneficial effects of Tai Chi in reducing anxiety and depressive symptoms in older adults is steadily increasing. Nonetheless, there remains a scarcity of studies directly comparing the clinical effectiveness of various Tai Chi exercises in addressing anxiety and depressive symptoms in older adults. Thus, this study aimed to systematically review and analyze the therapeutic efficacy of four types of Tai Chi interventions in enhancing anxiety and depressive symptoms in older adults.ii. Methods: During the period up to July 26, 2023, searches were conducted in the Web of Science, PubMed, the Cochrane Library, CNKI, and the Chinese Scientific Journal Database (VIP). The language scope encompassed both English and Chinese. Two independent reviewers conducted the literature review and data extraction. Review Manager 5.4 was employed for traditional metaanalysis and risk assessment, while version 15 of STATA software was used for generating evidence and funnel plots for network meta-analysis. This study was registered in PROSPERO number CRD 42023442270.iii. Result: In this analysis, a total of 20 studies were included, involving 1798 participants. The findings of the pairwise meta-analysis revealed that Tai Chi intervention was more effective than the control group in reducing anxiety (SMD: -1.19, 95% CI: -2.04, -0.34, p<0.05) and depression (SMD:-0.65, 95% CI: -0.95, -0.65, p<0.05) symptoms among older adults. The network meta-analysis specifically focused on anxiety symptoms and found that Yang-style Tai Chi (69.9%) had the most favorable outcome, followed by the 24-form Simplified Tai Chi (66.8%). In terms of depression symptoms, the Tai Chi Exercise Program (92.6%) had the highest performance, followed by Yangstyle Tai Chi (77.9%).The findings of this study imply that Tai Chi can have beneficial outcomes in the reduction of anxiety and depressive symptoms among older individuals. Specifically, when examining various forms of Tai Chi interventions, it was observed that Yang-style Tai Chi exhibited a greater efficacy in alleviating anxiety symptoms, whereas Tai Chi exercise programs demonstrated a higher effectiveness in improving depressive symptoms. Nonetheless, it is strongly advised that older adults select an exercise program that aligns with their interests and preferences, as this can